Clinical utility of 177Lu‐DOTATATE PRRT in somatostatin receptor‐positive metastatic medullary carcinoma of thyroid patients with assessment of efficacy, survival analysis, prognostic variables, and toxicity. Issue 3 (22nd November 2019) - Parghane, Rahul V.; Naik, Chinna; Talole, Sanjay; Desmukh, Anuja; Chaukar, Devendra; Banerjee, Sharmila; Basu, Sandip
Abstract: Background: The primary aim of this study was to evaluate the therapeutic efficacy and outcome of 177 Lu‐DOTATATE peptide receptor radionuclide therapy (PRRT) in somatostatin receptor‐positive metastatic medullary thyroid carcinoma (MTC), including progression‐free survival (PFS) and overall survival (OS), and also to determine the various prognostic variables. The secondary aim was toxicity assessment of PRRT in this group of patients. Methods: A total of 43 somatostatin receptor‐positive metastatic MTC patients, treated with 177 Lu‐DOTATATE PRRT in a large tertiary care center, were included in this analysis. After receiving the therapy, post‐treatment response evaluation was undertaken for symptomatic and biochemical responses (serum calcitonin) and imaging responses with 68 Ga‐DOTATATE, 18 F‐FDG PET‐CT, CeCT (PERCIST and RECIST 1.1 criteria). Calcitonin doubling time (CtnDT) was calculated by the American Thyroid Association calculator. The adverse events were graded according to the NCI‐CTCAE v5.0 criteria. The observed Kaplan‐Meier curves for both PFS and OS since first PRRT were compared with CtnDT (more than 24 months vs less than 24 months) by log‐rank (Mantel‐Cox) test. The prognostic variables were investigated for their association with CtnDT and response to PRRT using Cox proportional‐hazards model. RESULTS: The median OS was 26 months (95% CI 16.6‐35.3 months) and the median PFS 24 months (95%.CI: 15.1‐32.9 months). Following 177Lu‐DOTATATE PRRT, the observed median PFS and OS was longer in patients who had CtnDT more than 24 months compared to those with CtnDT less than 24 months (median PFS not yet reached vs 10 months and median OS 60 months vs 20 months). Assessing from the time‐point of first 177 Lu‐DOTATATE PRRT cycle, the patients with CtnDT more than 24 months had a significantly longer PFS ( P  < .001) and OS ( P  < .001) compared to those with less than 24 months. Less than 5 lesions, FDG uptake in lesions (SUVmax of <5) and patients alive at the time of analysis were the significant variables for association with CtnDT (more than 24 months). Out of 43 patients, 26 were responders (61%) and 17 nonresponders (39%) based upon PERCIST criteria, and 27 were responders (62%) while 16 patients were nonresponders (38%) based upon RECIST 1.1 criteria. The univariate analysis showed significant association between responses to PRRT with following prognostic variables: (a) size of lesions (<2 cm) and (b) FDG uptake in lesions (SUVmax of <5). PRRT was well tolerated in all patients without any major grade 3 or 4 toxicity. Conclusion: The results demonstrated that, 177 Lu‐DOTATATE is a potentially efficacious and safe therapeutic option in SSTR avid metastatic MTC patients.